Thinning Cspb2br5 Perovskite Down To Monolayers: Cs-Dependent Stability - İyikanat, Fadıl; Sarı, Emre; Sarı, Emre; Şahin, Hasan; Şahin, Hasan (American Physical Society, 2017)
Using first-principles density functional theory calculations, we systematically investigate the structural, electronic, and vibrational properties of bulk and potential single-layer structures of perovskitelike CsPb2Br5 crystal. It is found that while Cs atoms have no effect on the electronic structure, their presence is essential for the formation of stable CsPb2Br5 crystals. The calculated vibrational spectra of the crystal reveal that not only the bulk form but also the single-layer forms of CsPb2Br5 are dynamically stable. Predicted single-layer forms can exhibit either semiconducting or metallic character. Moreover, the modification of the structural, electronic, and magnetic properties of single-layer CsPb2Br5 upon formation of vacancy defects is investigated. It is found that the formation of Br vacancy (i) has the lowest formation energy, (ii) significantly changes the electronic structure, and (iii) leads to ferromagnetic ground state in the single-layer CsPb2Br5. However, the formation of Pb and Cs vacancies leads to p-type doping of the single-layer structure. Results reported herein reveal that the single-layer CsPb2Br5 crystal is a novel stable perovskite with enhanced functionality and a promising candidate for nanodevice applications.
Keywords: Perovskites; Monolayers; Light emitting diodes